Medical Students Vulnerability on Anxiety: Its Frequency and Associated Factors - Kusumadewi, Andrian Fajar; Marchira, Carla Raymondalexas; Widyandana, Doni; Wirasto, Ronny Tri; Dwidjoyono, Bernadeta Dinda Larasati; Phillabertha, Paulin Surya (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2024)
Abstract. Medical students are vulnerable populations at risk of mental health problems, particularly anxiety. Specifically during COVID-19, prevalence of anxiety among medical students increased rapidly and several factors affected its causes. This study aimed to find out the frequency of anxiety among medical students by using the TMAS questionnaire and factors that significantly contribute to anxiety levels. This cross-sectional study used simple random sampling of undergraduate medical students. The correlation between TMAS scores and several variables was analyzed with Spearman and Kruskall-Wallis correlation test and also multiple linear regressions. Among 275 respondents, the average age is 18.81 (SD 1.18), dominated by females (62.2%), in their first year (84.4%), non-scholarship (96.7%), lived in boarding houses (57.8%), and academic problem as the dominant cause of anxiety (46.5%). Later, 40.7% were anxious, then age and the year of study were found to be negatively correlated to their anxiety. A survey regarding the preferred form of anxiety therapy by medical students showed that 27.4% of respondents chose relaxation. These results are expected to help the development of future anxiety therapy based on the specific needs of medical students.Keywords: medical students, anxiety, demographic factors, TMAS, mental health